Chiral α‐Arylethanamines: An Organocatalyst for the Enantioselective α‐Amination of Branched Aldehydes. Issue 14 (19th March 2013) - Fu, Ji‐Ya; Wang, Qi‐Lin; Peng, Lin; Gui, Yong‐Yuan; Wang, Fan; Tian, Fang; Xu, Xiao‐Ying; Wang, Li‐Xin
Abstract: α‐Arylethanamines were investigated as organocatalysts for the α‐amination of branched aldehydes with azodicarboxylates. Optimization identified ( R )‐1‐(1‐naphthyl)ethanamine (1g ) as an effective and enantioselective organocatalyst; multifunctional chiral quaternary amino aldehydes were successfully obtained in excellent yields (up to 99 %) and with excellent enantioselectivities (up to 98 % ee ). Abstract : α‐Arylethanamine1g was found to be an effective and enantioselective organocatalyst for the α‐amination of branched aldehydes with azodicarboxylates. Multifunctional chiral quaternary amino aldehydes were successfully obtained in excellent yields (up to 99 %) and with excellent enantioselectivities (up to 98 % ee ).